2020
DOI: 10.1177/0034355220967093
|View full text |Cite
|
Sign up to set email alerts
|

The Protective Role of Character Strengths in COVID-19 Stress and Well-Being in Individuals With Chronic Conditions and Disabilities: An Exploratory Study

Abstract: Individuals with chronic conditions and disabilities, in response to stress associated with COVID-19, may experience a decrease in their overall well-being beyond that experienced by otherwise healthy individuals. Therefore, it is imperative to identify internal resources (e.g., character strengths) that can help them better manage COVID-19-related stress and enhance well-being in spite of COVID-19. This study explored the potential protective role of character strengths and virtues in moderating the negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…Consistent with the literature ( Yildirim et al, 2020a ; Yıldırım and Güler, 2020b ), the present evidence shows that perceived risk of coronavirus is a significant predictor of coronavirus stress in young adults. Furthermore, coronavirus stress significantly predicts spiritual well-being and meaning-based coping, which is consistent with previous research indicating that coronavirus stress is assorted with mental health problems and variables related to well-being (e.g., depression, anxiety, fear, burnout, and trauma; Fisher et al, 2020 ; Umucu et al, 2020 ; Yıldırım and Solmaz, 2020 ; Genç and Arslan, 2021). Perceived risk and stress may function to develop and form individuals’ stress-related behaviors ( Janz and Becker, 1984 ) because those with high levels of perceived risk and stress are more likely to focus on feelings, thoughts, and behaviors that influence their decisions and behaviors in the face of adverse experiences ( Cori et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the literature ( Yildirim et al, 2020a ; Yıldırım and Güler, 2020b ), the present evidence shows that perceived risk of coronavirus is a significant predictor of coronavirus stress in young adults. Furthermore, coronavirus stress significantly predicts spiritual well-being and meaning-based coping, which is consistent with previous research indicating that coronavirus stress is assorted with mental health problems and variables related to well-being (e.g., depression, anxiety, fear, burnout, and trauma; Fisher et al, 2020 ; Umucu et al, 2020 ; Yıldırım and Solmaz, 2020 ; Genç and Arslan, 2021). Perceived risk and stress may function to develop and form individuals’ stress-related behaviors ( Janz and Becker, 1984 ) because those with high levels of perceived risk and stress are more likely to focus on feelings, thoughts, and behaviors that influence their decisions and behaviors in the face of adverse experiences ( Cori et al, 2020 ).…”
Section: Discussionsupporting
confidence: 90%
“…The influence of the COVID-19 pandemic on well-being and mental health outcomes has been investigated in various studies. Taken together, the results of these studies reveal a positive association between coronavirus stress and depression, anxiety, fear, burnout, trauma, and other variables related to well-being and mental health outcomes ( Fisher et al, 2020 ; Umucu et al, 2020 ; Yıldırım and Solmaz, 2020 ; Genç and Arslan, 2021 ). For example, Arslan et al (2020) establish that coronavirus stress is positively associated with depression, anxiety, and somatization.…”
Section: Introductionmentioning
confidence: 79%
“…Higher levels of character strengths significantly and independently moderated the relationship between COVID-19-related stress and well-being. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…Such psychological consequences can have implications that are both short and long term, and are likely to increase the prevalence of anxiety, depression, insomnia and post-traumatic stress (Rogers et al, 2020;616-622) and other variables related to maintaining one's wellbeing (Umucu et al, 2020;Fisher et al, 2020;Arslan et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With regards to the various channels through which the pandemic has impacted psychological wellbeing, recent studies (i.e., Hamouche, 2020:4-5) have suggested that COVID-19-related psychological distress may be caused by multiple stressors (a combination of determinants) such as environmental (e.g., social disconnection, stigma; Xiang et al, 2020), organisational (e.g., job insecurity; Zhou et al, 2020;Brooks et al, 2020), as well as other supplementary factors (e.g., the risk of contagion, financial loss; Zhang et al, 2020;Wang et al, 2020). And the psychological burden that the ongoing pandemic has placed on individuals can be especially high for vulnerable demographics, including individuals with pre-existing mental health issues, patients with the virus and their families, the elderly, and healthcare workers (Rajkumar, 2020;Dubey et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%